Societal Marketing Orientation And Marketing Performance: The Mediating Role Of Key Market-Based Capabilities And The Moderating Effect Of Institutional Context - Ibrahim Balal, Siddig Balal (2011)
Societal issues appear to be increasingly important in today’s business climate. Response to these issues by adopting societal marketing orientation is expected to enable firms to gain better competitive advantage. However, literature search reveals that there is a lack of research offering valid measurement and a systematic framework that demonstrates the underlying mechanisms and contingencies through which societal marketing orientation can help firms to achieve that end. Using a priori approach the study intended to propose a valid measure of societal marketing orientation and to investigate the extent of this orientation among large manufacturing firms in Malaysia.